Genetic diagnosis of some root nodule bacteria isolated from leguminous Plants in Nineveh Governorate - Samar Alhayale; Mohammed Al-Shakarchi (College of Education for Pure Sciences, 2021)
The importance of atmospheric nitrogen-fixing bacteria The study aimed to isolate bacteria from the roots of plants From four areas of the city of Mosul the winter agriculture, season 2020-2021 and using biochemical tests and phenotypic and agricultural characteristics to diagnose bacterial isolates and study sensitivity and resistance of bacterial isolates to ten antibiotics. if the results showed that the highest percentage of resistance was to the two antibiotics, Trimethoprim, and streptomycin, at 100%, while The least resistance was to the two antivirals Gentamycin and Rifampicin by 20%. In addition to Studying The sensitivity and resistance of bacterial isolates to four heavy Metals, namely Mercury chloride (HgCl), Cobalt chloride (CoCl), Cadmium Chloride (CdCl), and nickel chloride (NiCl). The resistance was high with Cadmium chloride salt (CdCl) and the lowest salt Mercury Chloride (HgCl). PCR techniques were used to diagnose samples based on 16S rRNA sequence analysis and comparison of sequences resulting from DNA amplification with standard isolates within NCBI to detect new bacterial isolates